2022
DOI: 10.1002/pri.1935
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curved path walking compared to straight path walking in older adults with cognitive deficits: A systematic review and network meta‐analysis

Abstract: Objective: To determine whether the existing literature provides evidence that curved path walking time can be a reliable marker of cognitive impairment among older adults using a network meta-analysis (NMA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Walking on a curving path requires a transition time for changing the direction of walking and correction of balance [14]. Comprehensive analysis of curve walking may provide more information for detecting MCI among older adults than straight walking because curved path walking requires prediction of direction and postural control [14,15]. However, to our knowledge, no study has quantitatively compared the performance of HC versus MCI in straight and curve walking.…”
Section: Introductionmentioning
confidence: 99%
“…Walking on a curving path requires a transition time for changing the direction of walking and correction of balance [14]. Comprehensive analysis of curve walking may provide more information for detecting MCI among older adults than straight walking because curved path walking requires prediction of direction and postural control [14,15]. However, to our knowledge, no study has quantitatively compared the performance of HC versus MCI in straight and curve walking.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, cognitive function and set-shifting are thought to contribute to how older adults navigate a curved walking path, but not linear walking [ 15 ]. A systematic review on turning in older adults concluded that those with cognitive deficits had significantly longer walking times in both straight- and curved-path walking, and the relationship between performance and cognition was stronger for curved walking than for straight walking [ 16 ].…”
Section: Introductionmentioning
confidence: 99%